Wayang as an Instrument of Indonesia’s Nation Branding through Public Diplomacy - Khairunnisa, Najwa Dzakkiyah; Dermawan, Windy; Nurrochsyam, Mikka Wildha (Universitas Padjadjaran, 2026)
Wayang is a form of cultural heritage originating from Indonesia and is recognized in various local traditions, including Javanese, Sundanese, and Balinese cultures. Initially, Wayang functioned as a medium for communicating with ancestral spirits; however, over time, it has evolved into a medium for conveying messages, providing entertainment, and educating the public. Wayang has been officially acknowledged by UNESCO as an Intangible Cultural Heritage of Humanity. Indonesia’s appreciation of Wayang is further institutionalized through National Wayang Day, which is celebrated annually on 7 November. Nevertheless, Indonesia has yet to establish a distinctive “brand” that effectively introduces Wayang to international audiences. This study employs a qualitative approach based on a literature review. It aims to explore the potential of Wayang as Indonesia’s national brand. The findings indicate that Wayang has strong potential to serve as Indonesia’s brand, as it contributes to cultural preservation, supports economic development through the empowerment of related industries, promotes cultural tourism, and helps enhance Indonesia’s international image as a country rich in culture and values. Therefore, this article argues that the development of Wayang as Indonesia’s brand requires the synergy of three key pillars: the government, art and cultural organizations, and digitalization. These three pillars must work in tandem to successfully position Wayang as Indonesia’s national brand. Wayang merupakan warisan budaya yang berasal dari Indonesia. Wayang sangat familiar di berbagai kebudayaan Indonesia seperti kebudayaan Jawa, Sunda, dan Bali. Awalnya, Wayang digunakan sebagai media untuk berkomunikasi dengan roh nenek moyang namun seiring dengan berjalannya waktu, Wayang digunakan sebagai media untuk menyampaikan pesan, menghibur, dan mengedukasi massa. Wayang telah diakui sebagai warisan budaya tak benda yang luar biasa oleh UNESCO. Apresiasi Indonesia terhadap Wayang telah diperkuat dengan perayaan Hari Wayang Nasional setiap 7 November. Akan tetapi, Indonesia belum memiliki “merek” yang membuat masyarakat asing mengenal Wayang secara lebih baik. Penelitian ini, menggunakan pendekatan kualitatif dengan menggunakan studi pustaka. Kajian ini bertujuan untuk melakukan ekplorasi mengenai Wayang sebagai merek Indonesia. Hasil penelitian menunjukkan bahwa Wayang dapat digunakan sebagai “merek” Indonesia yang bermanfaat karena bisa mendukung proses pelestarian budaya, meningkatkan ekonomi yang bisa memberdayakan industri terkait, mendukung pariwisata budaya, dan memproyeksikan citra yang positif Indonesia sebagai negara dengan kebudayaan dan nilai-nilai yang kaya. Agar Wayang bisa maju sebagai merek Indonesia, terdapat tiga hal fundamental: pemerintah, organisasi seni dan budaya, serta proses digitalisasi. Tiga pilar tersebut perlu berjalan bersamaan untuk mewujudkan Wayang sebagai merek Indonesia.